Further Thoughts on Undang-Undang Laut Melaka: A Malay Mirror of the Archipelagic Homeland and Maritime Culture - Sudarman, Sudarman; Suryadi, Suryadi; Putra, Johan Septian (Journal of Al-Tamaddun, 2025)
The Malacca Sultanate and its dependencies, an important maritime kingdom in Southeast Asia’s Archipelago (c. 1400-1511), once had maritime law called Undang-undang Laut Melaka (The Malacca Maritime Code). This law suggests the authorisation of the Malacca Sultanate to its territorial waters. Through an extrinsic or contextualist historically oriented approach, this article examines the narrative of the Code together with its historical, political, and socio-cultural context, including the religious (Islamic) spirit. This study also traces the influences of the Code on the legal systems of other local maritime kingdoms in the Archipelago and its continued appreciation in the modern era. This paper argues that the primary motivations for creating the Code were the economic opportunities and political interests that arose from international trade flowing through the Strait of Malacca. This trade escalated complex economic and socio-cultural contestation among the local population and foreigners. The findings demonstrated that in tandem with its Land Code (Undang-undang Darat), the Malacca Maritime Code regulates not only criminal matters but also moral aspects related to trade and shipping activities in the Kingdom of Melaka. It integrates elements of Islamic law and local customs, serving as a source of inspiration for many other local kingdoms in the Archipelago to arrange their maritime codes. In contrast, the post-colonial era witnessed a decline in the Code’s recognition due to colonialism and limited literacy of the Archipelago’s people, leading to a degree of neglect of this significant indigenous intellectual heritage.